Stroke-associated dysarthria - Lan-Xin Lin; Lan-Xin Lin; Shun-Yu Yao; Shun-Yu Yao; Quan Chen; Quan Chen; Miao-Qiao Du; Miao-Qiao Du; Xu-Hui Kang; Xu-Hui Kang; Dai-Yi Jiang; Dai-Yi Jiang; et al. (Frontiers in Neurology)
A stroke can damage various regions of the brain. Damage to the upper motor neurons of the pyramidal tracts causes unilateral upper motor neuron dysarthria or spastic dysarthria. Dysarthria caused by a stroke is characterized by the coexistence of neurological deficits such as hemiparesis, hemiataxia, clumsiness of one hand, central facial paresis, and tongue deviation. In this review, we summarize the association between stroke and dysarthria, highlight the relevant methods used to measure stroke-associated dysarthria, and discuss specific exercises, advice, explanations, strategies, and psychological support.